Cardiotrophin‐1 is an anti‐inflammatory cytokine and promotes IL‐4–induced M2 macrophage polarization. Issue 6 (20th March 2019) - Carneros, David; Santamaría, Eva M.; Larequi, Eduardo; Vélez-Ortiz, Jose Miguel; Reboredo, Mercedes; Mancheño, Uxua; Perugorria, María Jesús; Navas, Plácido; Romero-Gómez, Manuel; Prieto, Jesús; Hervás-Stubbs, Sandra; Bustos, Matilde
ABSTRACT: Macrophages play a central role in tissue remodeling, repair, and resolution of inflammation. Macrophage polarization to Ml or M2 activation status may determine the progression or resolution of the inflammatory response. We have previously reported that cardiotrophin‐1 (CT‐1) displays both cytoprotective and metabolic activities. The role of CT‐1 in inflammation remains poorly understood. Here, we employed recombinant CT‐1 (rCT‐1) and used CT‐1 –null mice and myeloid‐specif ic CT‐1 transgenic mice to investigate whether CT‐1 might play a role in the modulation of the inflammatory response. We observed that CT‐1 deficiency was associated with enhanced release of inflammatory mediators and with stronger activation of NF‐κB in response to LPS, whereas the inflammatory response was attenuated in CT‐1 transgenic mice or by administering rCT‐1 to wild‐type animals prior to LPS challenge. We found that CT‐1 promoted IL‐6 expression only by nonhematopoietic cells, whereas LPS up‐regulated IL‐6 expression in both hematopoietic and nonhematopoietic cells. Notably, rCT‐1 inhibited LPS‐mediated soluble IL‐6R induction. Using IL‐6 −/− mice, we showed that rCT‐1 inhibited LPS‐induced TNF‐α and IFN‐γ response in an IL‐6–independent manner. Importantly, we demonstrated that CT‐1 primes macrophages for IL‐4–dependent M2 polarization by inducing IL‐4 receptor expression. Mechanistic analyses showed that the signal transducer and activator of transcription 3–suppressor of cytokine signaling 3 axis mediates this effect. Our findings support the notion that CT‐1 is a critical regulator of inflammation and suggest that rCT‐1 could be a molecule with potential therapeutic application in inflammatory conditions.—Carneros, D., Santamaría, E. M., Larequi, E., Vélez‐Ortiz, J. M., Reboredo, M., Mancheño, U., Perugorria, M. J., Navas, P., Romero‐Gómez, M., Prieto, J., Hervás‐Stubbs, S., Bustos, M. Cardiotrophin‐1 is an anti‐inflammatory cytokine and promotes IL‐4–induced M2 macrophage polarization. FASEB J. 33, 7578–7587 (2019). www.fasebj.org